Single incision-two port laparoscopic tubal ligation versus conventional three port laparoscopic tubal ligation: A prospective comparative study - Elçi Atılgan, Adeviye; Acar, Ali; Kılıç, Fatma; Altuntaş, Şükriye Leyla; Uzun, Asiye; Yaşar, Derya (Journal of Surgery and Medicine, 2021)
Background/Aim: Most women who have completed childbearing request tubal ligation, as it is an effective and irreversible form of contraception. Single incision laparoscopic surgery (SILS) which is currently standard in most surgical specialties, eliminates multiple port incisions and provides faster recovery with better cosmesis. However, there is less data about single incision laparoscopic bilateral tubal ligation. We aimed to compare the results of single-incision-two port laparoscopic tubal ligation and conventional three port laparoscopic tubal ligation. Methods: Patients who desired tubal ligation procedure as a contraceptive method were randomly allocated to two groups as single-incision-two port laparoscopic tubal ligation (Group 1) and conventional three port laparoscopic tubal ligation (Group 2) between April 2015 to January 2020 in the Obstetrics and Gynecology clinics of two university hospitals. A prospective comparative study was conducted, and sixty patients were included in each group, which were compared in terms of operation time, blood loss, length of hospital stay, complications, port site hernia, postoperative pain score, conversion rate, cosmesis and failure of sterilization. Results: There was no need to convert to open surgery in either group. Average blood loss was similar between the groups (107.6 ml vs 98.4 ml, P=0.14). Operating time was significantly longer in group 2 compared to group 1 (38 minutes vs. 26 minutes, P=0.02). Higher pain scores were observed in group 2 compared to group 1 at the 24th postoperative hour (2.21 vs 3.82, P=0.012). Patients in group 1 were more satisfied with the single incision in the umbilicus based on cosmetic outcome scores (4.88 vs 3.16, P=0.018). There were no reported intraoperative complications in either group. No port site hernias and failure of sterilization were observed in any of the patients. All patients were followed up for a mean of 19 months (range: 12–60 months). Conclusion: Single incision two port laparoscopic tubal ligation does not increase the risk of complications and appears safe. It provides better cosmetic outcomes and lower pain scores compared to conventional laparoscopy.